2009
DOI: 10.1007/s00128-009-9771-z
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Comet Assay for Genotoxic Effect Detection in Neotropical Fish Prochilodus lineatus (Pisces, Curimatidae)

Abstract: Toxicants on fish may induce genetic alterations that can be used as genotoxic markers. We evaluated DNA damage using alkaline comet assay applied on erythrocytes after in vivo exposure of Prochilodus lineatus to different concentrations of Cypermethrin (0.300, 0.150, 0.075 and 0.000 lg/L) as a probable chemical mutagen. The results revealed a significantly higher level of DNA damage at all concentrations of Cypermethrin tested compared to control and background level (p \ 0.05). We have standardized the techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 13 publications
0
36
1
Order By: Relevance
“…Their relationship may be useful as integrated environmental diagnostic tools and in developing control strategies and pollution prevention measures (Pathiratne et al 2008). The use of fish in freshwater and marine environments as bioindicators of environmental pollution has become more common in aquatic monitoring programs since the practice has proved useful in identifying environmental problems, mainly on the evaluation of the presence of potentially teratogenic and carcinogenic toxins (Simoniello et al 2009). Genotoxicity and endocrine disruption are the most worrying effects for their ecological implications in aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Their relationship may be useful as integrated environmental diagnostic tools and in developing control strategies and pollution prevention measures (Pathiratne et al 2008). The use of fish in freshwater and marine environments as bioindicators of environmental pollution has become more common in aquatic monitoring programs since the practice has proved useful in identifying environmental problems, mainly on the evaluation of the presence of potentially teratogenic and carcinogenic toxins (Simoniello et al 2009). Genotoxicity and endocrine disruption are the most worrying effects for their ecological implications in aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained by Campana et al (1999) demonstrated the genotoxic effects of lambda-cyhalothrin on erythrocytes of Cheirodon interruptus interruptus. Simoniello et al (2009) reported that cypermethrin showed a signifi cantly higher level of DNA damage in the fi sh species Prochilodus lineatus after in vivo exposure to different concentrations of cypermethrin.…”
Section: Resultsmentioning
confidence: 99%
“…Information on the genotoxic effects of pyrethroid insecticides on fi sh species is limited. However, some studies have demonstrated that synthetic pyrethroids are genotoxic to fi sh (Campana et al, 1999;Çavas and Ergene-Gözükara, 2003;Simoniello et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Disturbances in the DNA molecule such as adducts, single, and double-strand breaks may cause permanent damage that induces MN, being then an excellent biomarker to evaluate any permanent DNA damage (Vanzella et al, 2007). Increased MN frequencies in blood cells of the Neotropical fish Prochilodus lineatus exposed to diesel water soluble fraction under acute and subchronic conditions, demonstrated that MN is an efficient endpoint for detecting mutagenic compounds in water (Simoniello et al, 2009).…”
Section: Discussionmentioning
confidence: 99%